Unlocking plant resilience: Advanced epigenetic strategies against heavy metal and metalloid stress - Iqbal, Babar; Ahmad, Naveed; Li, Guanlin; Jalal, Arshad [UNESP]; Khan, Ali Raza; Zheng, Xiaojun; Naeem, Muhammad; Du, Daolin (Elsevier, 2024)
The escalating threat of heavy metal and metalloid stress on plant ecosystems requires innovative strategies to strengthen plant resilience and ensure agricultural sustainability. This review provides important insights into the advanced epigenetic pathways to improve plant tolerance to toxic heavy metals and metalloid stress. Epigenetic modifications, including deoxyribonucleic acid (DNA) methylation, histone modifications, and small ribonucleic acid (RNA) engineering, offer innovative avenues for tailoring plant responses to mitigate the impact of heavy metal and metalloid stress. Technological advancements in high-throughput genome sequencing and functional genomics have unraveled the complexities of epigenetic regulation in response to heavy metal and metalloid contamination. Recent strides in this field encompass identifying specific epigenetic markers associated with stress resilience, developing tools for editing the epigenome, and integrating epigenetic data into breeding programs for stress-resistant crops. Understanding the dynamic interaction between epigenetics and stress responses holds immense potential to engineer resilient crops that thrive in environments contaminated with heavy metals and metalloids. Eventually, harnessing epigenetic strategies presents a promising trajectory toward sustainable agriculture in the face of escalating environmental challenges. Plant epigenomics expands, the potential for sustainable agriculture by implementing advanced epigenetic approaches becomes increasingly evident. These developments lay the foundation for understanding the growing significance of epigenetics in plant stress biology and its potential to mitigate the detrimental effects of heavy metal and metalloid pollution on global agriculture.
Keywords: DNA methylation; Epigenetic engineering; Histone acetylation; Stress tolerance